1989
DOI: 10.1017/s0022215100110473
|View full text |Cite
|
Sign up to set email alerts
|

Serum antibodies against respiratory tract viruses: A prospective three-year follow-up from birth

Abstract: Acute otitis media (AOM) has been epidemiologically related to viral respiratory tract infections, and viral antigens have also been detected in middle ear secretion in some AOM episodes. Successive serum samples from children followed prospectively for three years from birth were analysed for IgG antibodies against respiratory syncytial virus (RSV), adenoviruses and influenza A virus. Values from serum antibody activity gradually decreased during the first six months of life, followed by a gradual increase. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
3
7
0
Order By: Relevance
“…first 2 years of life, of which 13 were associated with mild URTI and seven were found during routine sampling of clinically healthy infants. The prevalence of RSVspecific serum IgG antibodies in infants' samples at the age of 18 or 24 months indicated that the majority had experienced at least one RSV infection in the first 2 years of life, in accordance with other cohort studies [Harsten et al, 1989;Moylett and Piedra, 1999]. Based on the literature, it was expected that few primary RSV infections would be asymptomatic [Collins et al, 1996], most infections would be associated with URTI, and 25-40% with RSV bronchiolitis [Martin et al, 1978;Hall et al, 1979;Weigl et al, 2001].…”
Section: Discussionsupporting
confidence: 89%
“…first 2 years of life, of which 13 were associated with mild URTI and seven were found during routine sampling of clinically healthy infants. The prevalence of RSVspecific serum IgG antibodies in infants' samples at the age of 18 or 24 months indicated that the majority had experienced at least one RSV infection in the first 2 years of life, in accordance with other cohort studies [Harsten et al, 1989;Moylett and Piedra, 1999]. Based on the literature, it was expected that few primary RSV infections would be asymptomatic [Collins et al, 1996], most infections would be associated with URTI, and 25-40% with RSV bronchiolitis [Martin et al, 1978;Hall et al, 1979;Weigl et al, 2001].…”
Section: Discussionsupporting
confidence: 89%
“…Our result, that approximately 85% of all children were seropositive for RSV by 3 y of age, is in line with earlier studies [11,12]. Due to our study design, we may have missed early RSV infections (not inducing IgG antibodies in significant amounts) since one-third of children were recruited into the study during their second year of life [7].…”
Section: Discussionsupporting
confidence: 89%
“…It is known that the presence of maternal antibodies affects infants' ability to develop an immune response to RSV [10], and a substantial proportion of hospitalized infants experiencing their first RSV infection do not show a rise in antibody titres [11]. In those infected, antibody titres are age dependent, showing marked increase after 6 to 9 mo of age [11,12]. Thus, lack of antibodies is not always an indication of no previous exposure [11].…”
Section: Discussionmentioning
confidence: 99%
“…This is likely to decrease during later childhood because prevalences up to 13% have been reported in adults (30). At the age of 18 months, most children (75%) will have been infected with RSV at least once (31). The prevalence of rhinovirus increases slowly to more than 50%.…”
Section: Discussionmentioning
confidence: 99%